The effect of weakened resilience on food insecurity in protracted crisis: the case of South Sudan - Lokosang, Lailà B.; Ramroop, Shaun; Zewotir, Temesgen (BioMed Central, 2016)
Background: This study aims to determine predictors of food insecurity in a typical setting where resilience of population is weakened as a result of protracted crises. South Sudan is used as a case study. The rationale of the study is anchored on the perception that food insecurity risk is a function of weak resilience, which in turn is a function of the absence of a combination of certain characteristics and livelihood endowments of a household or a population. Analysis explores the use of SAS® SURVEYLOGISTIC procedure, as it has been established to be useful in analysis of data from sample surveys. The procedure is known for its valid statistical inference. Results: Employing a survey logistic model with generalised logit link function determined all fitted fixed effects to be statistically significant. Analysis showed that characteristics of households and agriculture (including livestock and fishing) were typically associated with acceptable level of food consumption and implying that the absence of these factors demonstrated weakened resilience and thus increased risk of food insecurity. Analysis also examined the odds of each level of fixed effect compared to the reference level in relation to the food consumption score (the response or outcome variable). Findings were interesting, but largely confirmed what was expected (see Table 5). For instance, it was found out that households headed by younger adults aged 17 years or less fared three times worse than those aged 60 years and above. It was also shown that smaller households fared better than larger ones. The odds of a household with three or less members were twice as worse as those with seven or more members. Conclusion: We conclude that the method exerted reasonable statistical efficiency for fulfilling the study end, thus providing sufficient evidence for food security analysts and development policy makers in the course of developing appropriate interventions for early preparedness and crises response.
DOI 10.1186/s40066-016-0051-y
Keywords: Food consumption score; Vulnerability; Complex sample; Fixed effects; Generalised logit; Prediction